Sonotope patterns within a mountain beech forest of Northern Italy: a methodological and empirical approach - Farina, Almo; Mullet, Timothy C. (Frontiers in Ecology and Evolution, 2024)
According to the Sonotope Hypothesis, the heterogenous nature of the acoustically sensed, but not yet interpreted, environmental sounds (i.e., sonoscape) is created by the spatial and temporal conformation of sonic patches (sonotopes) as recently been described in a Mediterranean rural landscape.We investigated the Sonotope Hypothesis in a mountain beech forest of the Northern Apennines, Italy that is notoriously poor in soniferous species. Our aim was to test whether sonotopes were temporally distinct over seasonal and astronomical timeframes and spatially configured in relation to vegetation variables. We used the Acoustic Complexity Index (ACItf) to analyze the heterogeneity of sonic information gathered from an array of 11 sound recorders deployed within a lattice of 11, 4-ha hexagonal sample sites distributed throughout a 48-ha managed beech forest. We visualized and described the temporal patterns of ACItf between seasons (May -June and July-August 2021),